2009 IEEE 9th Malaysia International Conference on Communications (MICC) 2009
DOI: 10.1109/micc.2009.5431488
|View full text |Cite
|
Sign up to set email alerts
|

RLMS algorithm for fixed or adaptive beamforming

Abstract: This paper presents a flexible method of achieving either fixed or self-adaptive antenna beamforming. It involves the use of the array image factor ' d A , which interfaces the Recursive Least Squares (RLS) and Least Mean Squares (LMS) sections in cascade to form the RLMS beamforming algorithm. It is shown that an accurate fixed beam can be obtained by simply setting the elements of ' d A with prescribed values corresponding to the required direction. Moreover, the beam direction can also be made adaptive to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The performance of the RLMS beamforming algorithm has previously been presented in [4,[10][11][12]. These earlier results are based on the RLMS algorithm being implemented with full precision for operation under various channel conditions, including additive white Gaussian noise, and cochannel interference.…”
Section: B Simulated Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance of the RLMS beamforming algorithm has previously been presented in [4,[10][11][12]. These earlier results are based on the RLMS algorithm being implemented with full precision for operation under various channel conditions, including additive white Gaussian noise, and cochannel interference.…”
Section: B Simulated Algorithmsmentioning
confidence: 99%
“…Furthermore, RLMS can operate with a noisy reference signal. As described in, [11,12] RLMS can be used to achieve an accurate fixed beam by prior setting the elements of F with prescribed values for the required direction. On the other hand, the beam direction can also be made adaptive to automatically track the target signal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it is desired to utilize smart antennas array in 60-GHz band, both omnidirectional and directional antennas will be considered for analysis. Currently, there are many researches on beamforming techniquesbased spatial reuse schemes [2][3][4]. It is shown that the multibeam smart antennas are more suitable for 60-GHz WPANs based on the considerations of low cost and low complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are many researches on spatial reuse schemes based on beamforming techniques [2,3]. Although the short wavelength of the 60GHz band makes it possible to realize small size of antenna array at terminal devices, it appears some other problems.…”
Section: Introductionmentioning
confidence: 99%